Motives for Dissertation Research at the Intersection Between Rural Education and Curriculum and Instruction - Craig B. Howley; Jaqueline Yahn (Journal of Research in Rural Education, 2014)
Dissertation literature focusing on issues of curriculum and instruction (C&I) in rural schools has substantially increased since 1987. We located 580 possibly rural C&I dissertations and subsequently identifi ed 194 as probably rural; of these we were able to obtain digital copies of 188 full-length studies. Our purpose was to characterize the explicit motives evident in the discourse of these 188 works. Kenneth Burke's A Grammar of Motives supplied the theoretical framework supporting our consensus coding of each dissertation as primarily refl ecting one of four rural motives: (1) rural knowledge motive, (2) rural justice motive, (3) rural caring motive, and (4) rural convenience motive. The motive characterizing more than half of the dissertations was rural knowledge whereas the motive characterizing the fewest dissertations was rural caring. Our interpretation speculates about the tendency for C&I studies to focus on improvement, especially in face of the purported defi ciency of rural people and places. Detailed analysis of 188 dissertations also gave us a basis to offer critique of dissertation research in the fi eld of rural education with recommendations for dissertation students and the faculty who support dissertation work.